Lack of association of antihypertensive drugs with the risk and severity of COVID-19: A meta-analysis. Issue 5 (May 2021) - Ren, Lu; Yu, Shandong; Xu, Wilson; Overton, James L; Chiamvimonvat, Nipavan; Thai, Phung N.
Highlights: The usage of antihypertensive drugs is not associated with the risk and severity of COVID-19. Hypertensive patients with COVID-19 benefit from prior usage of angiotensin-converting enzyme inhibitors/angiotensin receptor blockers. Abstract: Background: The association of antihypertensive drugs with the risk and severity of COVID-19 remains unknown. Methods and Results: We systematically searched PubMed, MEDLINE, The Cochrane Library, Cochrane Central Register of Controlled Trials (CENTRAL), ClinicalTrials.gov, and medRxiv for publications before July 13, 2020. Cohort studies and case-control studies that contain information on the association of antihypertensive agents including angiotensin-converting enzyme inhibitors (ACEIs), angiotensin II receptor blockers (ARBs), calcium-channel blockers (CCBs), β-blockers, and diuretics with the risk and severity of COVID-19 were selected. The random or fixed-effects models were used to pool the odds ratio (OR) with 95% confidence interval (CI) for the outcomes. The literature search yielded 53 studies that satisfied our inclusion criteria, which comprised 39 cohort studies and 14 case-control studies. These studies included a total of 2, 100, 587 participants. We observed no association between prior usage of antihypertensive medications including ACEIs/ARBs, CCBs, β-blockers, or diuretics and the risk and severity of COVID-19. Additionally, when only hypertensive patients were included, the severity and mortality were lower with prior usage of ACEIs/ARBs (overall OR of 0.81, 95% CI 0.66−0.99, p < 0.05 and overall OR of 0.77, 95% CI 0.66−0.91, p < 0.01). Conclusions: Taken together, usage of antihypertensive drugs is not associated with the risk and severity of COVID-19. Based on the current available literature, it is not recommended to abstain from the usage of these drugs in COVID-19 patients. Registration: The meta-analysis was registered on OSF (https://osf.io/ynd5g ).